Development of a technology for manufacturing a heat-shielding structure on nitrogen cryocontainers, excluding heat transfer through gas - Zhun, H. H.; Starikov, V. V.; Koverya, V. P. (My University, 2022)
One of the important stages in the creation of the scientific and technical foundations for the calculation, de-sign and manufacturing technology of the lowest heat-conductivity thermal protection from screen-vacuum thermal insulation (SVTI) is the development of a process for achieving the optimal vacuum Р₀ ≤ 10⁻³ Pa in the SVTI layers, since at this pressure, thermal conductivity (λeff) through the SVTI is carried out only due to the radiant (λrad) and contact-conductive (λk.k) components. It is proposed to obtain such a pressure in thermal insulation by using cushioning material in it, which was previously degassed in a separate vacuum chamber at 370–380 K for 12 h in order to remove water molecules from its structure and then replace them with nitrogen molecules. These molecules have 3–4 times less heat of adsorption; therefore they are pumped out faster. As a result, it becomes possible to accelerate (by ~ 20 h) to achieve optimal vacuum in thermal insulation, as well as 11% lower effective thermal conductivity [equal to (14.1–14.3)∙10⁻⁵ W/(m∙K)]. The analysis carried out (according to the developed methodology) showed that the achieved optimal effective thermal conductivity of thermal insulation in a cryocontainers is determined by 33% of radiant thermal conductivity [4.7∙10⁻⁵ W/(m∙K)] and 67% of the contact-conductive component [9.4∙10⁻⁵ W/(m∙K)].

Одним з важливих етапів створення науково-технічних основ розрахунку, проєктування та технології виготовлення найбільш низькотеплопровідного теплозахисту з екранно-вакуумної теплоізоляції (ЕВТІ) є розробка процесу досягнення в шарах ЕВТІ оптимального вакууму Р₀ ≤ 10⁻³ Па, оскільки при цьому тиску теплопровідність (λeff) через ЕВТІ здійснюється тільки за рахунок променевої (λrad) та контактно-кондуктивної (λk.k) складових. Запропоновано отримувати цей тиск у теплоізоляції шляхом використання в ній прокладкового матеріалу, який попередньо в окремій вакуумній камері при температурі 370–380 К піддавався дегазації протягом 12 годин з метою видалення з його структури молекул води та подальшого їх заміщення на молекули азоту. Дані молекули мають у 3–4 рази меншу теплоту адсорбції, тому швидше відкачуються. В результаті стає можливим прискорено (на ~ 20 годин) досягати в теплоізоляції оптимального вакууму, а також меншу на 11% ефективну теплопровідність [що дорівнює (14,1–14,3)∙10⁻⁵ Вт/(м∙К)]. Проведений (за розробленою методикою) аналіз показав, що оптимальна ефективна теплопровідність теплоізоляції в кріопосудині обумовлюється на 33% променевою теплопровідністю [4,7∙10⁻⁵ Вт/(м∙К)] і на 67 % контактно-кондуктивною складовою [9,4∙10⁻⁵ Вт/(м∙К)].
Технологія виготовлення теплозахисної ізоляції азотних кріопосудин, що виключає теплоперенесення через газ
Keywords: cryocontainer; thermal insulation; liquid nitrogen; vacuum; екранно-вакуумна теплоізоляція; теплопровідність; рідкий азот; кріопосудина